THE DEVELOPMENT, THE CHEMICAL COMPOSITION AND THE SENSORY ANALYSIS OF QUINOA BARS (CHENOPODIUM QUINOA WILLD.) SUBJECTED TO DIFFERENT THERMAL TREATMENTS - Marjana Radünz; Júlia Nickel; Márcia Arocha Gularte; Elizabete Helbig (Universidade do Estado do Rio de Janeiro, 2016)
Objective: Considering the high nutritional value of quinoa grain, with protein composed by all essential amino acids, this study aimed to develop cereal bars elaborated with this grain after two different thermal processing, to evaluate the chemical composition and to verify the preference between the bars using a sensory analysis. Material and methods: The bars were prepared with quinoa submitted to hydration process in water and toasting process. It was performed the chemical composition (moisture, ash, crude fiber, protein, lipids and carbohydrates) of the grains and quinoa bars. The sensory analysis for verification of preference between the bars was performed by hedonic scale of 7 points and purchase intent by 5-point scale. Results: The lipid, crude fiber, ash and carbohydrate contents of quinoa grains had variations after thermal processing. Between the bars, there were significant differences in protein, ash and carbohydrates amount. In the sensorial analysis, the bar containing toasted quinoa grains was preferred, with good acceptability index (85%), while the bar containing hydrated quinoa grains presented a lower rate (66.34%), not being accepted, mainly because of its softened texture. The same occurred in purchase intent, which consumers showed that would probably buy the bar elaborate with toasted grains and would maybe buy the bar containing hydrated grains. Conclusion: The cereal bar produced with toasted quinoa grains is the best formulation for product development, which has viability to be commercialized, as it obtained a good acceptability index. DOI: 10.12957/demetra.2016.22384